The Role of Quantum Tunneling in Evolutionary Chemistry and the Function of Biomolecular Nanomachines in Nanoscale Systems - Kumar, Rajendra (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Quantum tunneling — the ability of particles to cross classically forbidden energy barriers — has emerged as an important mechanistic element in chemistry and biology, spanning from prebiotic reaction pathways and spontaneous mutations to enzyme catalysis and charge transfer in biomolecular machines. Separately, biomolecular nanomachines (molecular motors such as ATP synthase, kinesin, myosin and engineered molecular devices) convert chemical free energy into directed mechanical work at the nanoscale; their operation depends on tight coupling of chemical, mechanical, and sometimes quantum events. This article synthesizes current understanding of how quantum tunneling contributes to evolutionary chemistry (including origins-of-life scenarios and mutation mechanisms) and how quantum and classical processes co-operate within biomolecular nanomachines. The experimental evidence, theoretical frameworks (open quantum systems, tunneling-corrected transition-state theory, kinetic isotope effects), and emerging direction are highlighted. The cross-talk between tunneling physics and nanoscale machine function may be consequential.